The CHD8 overgrowth syndrome: A detailed evaluation of an emerging overgrowth phenotype in 27 patients. Issue 4 (13th November 2019) - Ostrowski, Philip J.; Zachariou, Anna; Loveday, Chey; Beleza‐Meireles, Ana; Bertoli, Marta; Dean, John; Douglas, Andrew G. L.; Ellis, Ian; Foster, Alison; Graham, John M.; Hague, Jennifer; Hilhorst‐Hofstee, Yvonne; et al.
Abstract: CHD8 has been reported as an autism susceptibility/intellectual disability gene but emerging evidence suggests that it additionally causes an overgrowth phenotype. This study reports 27 unrelated patients with pathogenic or likely pathogenic CHD8 variants (25 null variants, two missense variants) and a male:female ratio of 21:6 (3.5:1, p < .01). All patients presented with intellectual disability, with 85% in the mild or moderate range, and 85% had a height and/or head circumference ≥2 standard deviations above the mean, meeting our clinical criteria for overgrowth. Behavioral problems were reported in the majority of patients (78%), with over half (56%) either formally diagnosed with an autistic spectrum disorder or described as having autistic traits. Additional clinical features included neonatal hypotonia (33%), and less frequently seizures, pes planus, scoliosis, fifth finger clinodactyly, umbilical hernia, and glabellar hemangioma (≤15% each). These results suggest that, in addition to its established link with autism and intellectual disability, CHD8 causes an overgrowth phenotype, and should be considered in the differential diagnosis of patients presenting with increased height and/or head circumference in association with intellectual disability.